If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -4 = 4n + 6 Reorder the terms: -4 + 6n = 4n + 6 Reorder the terms: -4 + 6n = 6 + 4n Solving -4 + 6n = 6 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -4 + 6n + -4n = 6 + 4n + -4n Combine like terms: 6n + -4n = 2n -4 + 2n = 6 + 4n + -4n Combine like terms: 4n + -4n = 0 -4 + 2n = 6 + 0 -4 + 2n = 6 Add '4' to each side of the equation. -4 + 4 + 2n = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 2n = 6 + 4 2n = 6 + 4 Combine like terms: 6 + 4 = 10 2n = 10 Divide each side by '2'. n = 5 Simplifying n = 5
| x/3-7=-13 | | 8(x+1)=5x-16 | | 9l=6.2 | | 8(7-x)= | | 11-(x+8)=8x-6 | | 9.75-p=64 | | 4x^4-18x^3+42x^2-108x+108= | | -13X+20=-11X | | V=1385n+18790 | | A^2=2209 | | 5x+4g=c | | 8=-3x+2(x-4) | | 6-2x=22 | | 4g+7=4g-1 | | 4(2x+1)-3(y+1)= | | -2=-1.75+k | | 12r^2-75=0 | | -2=7+k/(-4) | | 4(w+3)=w- 15 | | X=3x+12 | | 40+400+1= | | 7(3-y)=-3x+4 | | 21x+6=17x-16 | | -d^2+18d-81=0 | | -13X+20=-11 | | (5x-20)=3x | | 7h-3h-6=6 | | 5(x-1)(x+4)(2x-3)=0 | | -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= |